Effect of mucin on β-lactoglobulin and lactose interaction - Yılmaz, Hilal; Yılmaz, Hilal (Cambridge Univ Press, 2023)
Functions of mucin, as the major macromolecular component in saliva or gastric fluids, are drawing increasing attention in the context of understanding the oral processing or digestion of dairy foods at the molecular level. This study was designed to investigate the interactions between beta-lactoglobulin (BLG)-lactose, mucin-lactose and BLG-lactose-mucin at the molecular level under different temperature and pH conditions using fluorescence spectroscopy in combination with scanning electron microscopes (sem). It is the first study of its kind. There was no lactose-dependent quenching on BLG fluorophore in the range of 0-10 mM lactose concentration. On the contrary, there was a continuous increase in the fluorescence intensity of the BLG protein when the lactose concentration increased, especially at 25?. BLG-lactose complex became thermally unstable at 37 and 45?. Moreover, BLG exhibited a pH dependent conformational change and had higher fluorescence intensity at pH 3 than pH 6.8. The fluorescence result was in correspondence with sem images where we observed lactose crystals gathering around and on the BLG molecule, but lactose molecules could not be seen in the presence of mucin. It was anticipated that mucin molecules interacted with BLG-lactose complex via electrostatic attraction and formed an extra protective layer around the BLG molecules to avoid solvent exposure.
Keywords: Fluorescence; Lactose; Mucin; Ph; Sem; Temperature; Beta-Lactoglobulin